BIOLOGY OF Trissolcus latisulcus Crawford (Hymenoptera: Scelionidae), AN EGG PARASITOID OF Chrysocoris javanus Westw (Hemiptera: Scutelleridae) - Damayanti Adidharma; Y.D. Ciptadi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
The biology of Trissolcus latisulcus Crawford was studied on eggs of Chrysocoris javanus Westw (Hemiptera: Scutelleridae) which is a serious pest of Jatropha curcas L.. The aim of this study was to investigate the biology of Trissolcus latisulcus as a basic knowledge for developing a more suitable biological control programme in controlling the pest C. javanus. The current laboratory study was designed to evaluate developmental duration from egg to adult of C. javanus under room condition temperature: 28.18 + 0.59°C and RH 56.33 + 4.27%. The results showed that the life cycle of immature T.latisulcus consisted of egg, larva ( three instars) , prepupa, pupa. The longevity period of each stadium was one day, four days, one day, and five days respectively. The development time from egg to adult took 12.66 + 1.22 days for female and 11.91 ± 0.73 days for males.The life time from egg to dead adult was 17.40 + 7.38 days for female and 23.70 ± 9.49 days for males. The egg of T.latisulcus was stalked type, the first instar larva was teleaform type and the third instar larva was hymenopteriform type. Keywords: Jatropha curcas L, Chrysocoris javanus Westw, Trissolcus latisulcus Crawford ,parasitoid eggs